EPIDEMIOLOGICAL STUDY OF MERCURY EXPOSURE EFFECT ON COMMUNITYâS HEALTH AT SMALL-SCALE GOLD MINING LOCATIONS (CASE STUDY ON 4 AREAS IN INDONESIA) - Widya Dewi Kusumah, Siska
Mercury released from ASGM activities may expose surrounding communities and induces mercury intoxication. Diagnostic tools to detect mercury intoxication, such as Human Biomonitoring (HBM) test had not considered any confounding factor that can affect its accuracy. This research calculated the log odds of mercury intoxication, identify risk factors, including and confoundings factors that may affect the accuracy of HBM. Cross sectional studies were conducted in 4 districts in Indonesia (WG, MR, KB and DH). Mercury concentrations in ambient air were measured using lumex USA, in inhaled air using personal sampler, and in consumable goods (rice, drinking water, fish and groceries) using ICP-MS to approximate mercury intakes. Interviews, HBM test and health assessment were done on 216 respondents to determine their intoxication status. The log odd ratio of mercury intoxication was estimated using logistic regression analysis. The results showed that daily total mercury intake were higher than the WHO’s allowable intakes in most respondents in all areas, with the highest intake in WG District (1,82 ± 1,6 µg/Kg.Day). Average mercury concentrations in urine, hair, and nail samples were also higher than the WHO standard in most areas with the highest average also found in WG district. Proportion of respondents having mercury intoxication were higher in the mining group (44%) as compared to the non miners (12%). Adjusted log odd ratio of mercury intoxication among miners was 0,693 and for the non-miners was -0,261. Body mass index, gender, other illnesses, smoking habit, and gender were found to be confounding factors with magnitude more than 44% in all area. Therefore, confounding factors need to be controlled to increase the validity and the accuracy of the intoxication status as determined by the HBM method.